Actuaciones pedagógicas e investigativas en la adquisición del inglés en los estudiantes de formación docente - Pardo Espejo, Nelly Estella (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The present article describes the academic and research processes for teaching and learning English in the Basic Education degree with emphasis in Mathematics, Humanities and Spanish Language of the Faculty of Distance Studies of the UPTC. Therefore, it is based on some educational policies of the MEN related to foreign language teaching in Colombia, as well as the pedagogical implications and inves- tigative studies of English at a teacher training program in the distance education modality.